2015
DOI: 10.1002/macp.201500356
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide–Poly(ethylene glycol) methyl ether methacrylate Nanocomposite Hydrogels

Abstract: In this paper, covalently linked graphene oxide–poly(ethylene glycol) methyl ether methacrylate–reversible addition‐fragmentation chain transfer (GO–PEGMEMA–RAFT) and physically mixed GO–PEGMEMA hydrogel nanocomposites are synthesized. Spectroscopic and imaging techniques such as UV–vis, Fourier transform infrared, Raman spectroscopy, and transmission electron microscopy show that the PEGMEMA is successfully grafted on GO sheets. The rheology of the nanocomposites is studied by small angle oscillatory shear, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Accordingly, these aggregated particles can activate the lubricating role of graphene more noticeably, resulting in the facilitation of movements of polymer chains and, consequently, a decrease in the elastic response of NC‐1 nanocomposite. A similar observation has been reported by other researchers for the case of GO nanocomposite 38 …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Accordingly, these aggregated particles can activate the lubricating role of graphene more noticeably, resulting in the facilitation of movements of polymer chains and, consequently, a decrease in the elastic response of NC‐1 nanocomposite. A similar observation has been reported by other researchers for the case of GO nanocomposite 38 …”
Section: Resultssupporting
confidence: 92%
“…It has been reported that graphene can either act as a reinforcing agent or a lubricant one in a composite system 27,36‐38 . The reinforcement degree of graphene on a polymer matrix is highly connected to the interfacial interaction of graphene and polymer, quality of dispersion of graphene in the polymer matrix, changes in the degree of crystallinity, and also the crystalline structure of polymers in the presence of graphene 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we can also achieve χ c (the number of micelles per unit volume) by the following equation [26]:χc=([SDS]NaggCMC)*nV…”
Section: Resultsmentioning
confidence: 99%
“…Thus, improving the mechanical properties and extending the practical applications of hydrogels have been a significant topic in the field of hydrogel science . In this regard, great efforts have been contributed by designing the unique structure and/or introducing effective mechanism for energy dissipation to develop mechanically tough hydrogels, such as nanocomposite (NC) hydrogels, double‐network (DN) hydrogels, tetra‐arm poly(ethylene glycol) hydrogels, slide‐ring hydrogels, microgel‐reinforced hydrogels, and polyampholytes hydrogels …”
Section: Introductionmentioning
confidence: 99%